Impact of carbendazim on cellular growth, defence system and plant growth promoting traits of Priestia megaterium ANCB-12 isolated from sugarcane rhizosphere - Sharma, Anjney; Song, Xiu-Peng; Singh, Rajesh Kumar; Vaishnav, Anukool; Gupta, Saurabh; Singh, Pratiksha; Guo, Dao-Jun; Verma, Krishan K.; Li, Yang-Rui (Frontiers in Microbiology, 2022)
Agrochemicals are consistently used in agricultural practices to protect plants from pathogens and ensure high crop production. However, their overconsumption and irregular use cause adverse impacts on soil flora and non-target beneficial microorganisms, ultimately causing a hazard to the ecosystem. Taking this into account, the present study was conducted to determine the high dosage of fungicide (carbendazim: CBZM) effects on the rhizobacteria survival, plant growth promoting trait and reactive oxygen species (ROS) scavenging antioxidant enzyme system. Thus, a multifarious plant growth promoting rhizobacteria (PGPR) isolate, ANCB-12, was obtained from the sugarcane rhizosphere through an enrichment technique. The taxonomic position of the isolated rhizobacteria was confirmed through 16S rRNA gene sequencing analysis as Priestia megaterium ANCB-12 (accession no. ON878101). Results showed that increasing concentrations of fungicide showed adverse effects on rhizobacterial cell growth and survival. In addition, cell visualization under a confocal laser scanning microscope (CLSM) revealed more oxidative stress damage in the form of ROS generation and cell membrane permeability. Furthermore, the increasing dose of CBZM gradually decreased the plant growth promoting activities of the rhizobacteria ANCB-12. For example, CBZM at a maximum 3,000 μg/ml concentration decreases the indole acetic acid (IAA) production by 91.6%, ACC deaminase by 92.3%, and siderophore production by 94.1%, respectively. Similarly, higher dose of fungicide enhanced the ROS toxicity by significantly (p < 0.05) modulating the stress-related antioxidant enzymatic biomarkers in P. megaterium ANCB-12. At a maximum 3,000 μg/ml CBZM concentration, the activity of superoxide dismutase (SOD) declined by 82.3%, catalase (CAT) by 61.4%, glutathione peroxidase (GPX) by 76.1%, and glutathione reductase (GR) by 84.8%, respectively. The results of this study showed that higher doses of the fungicide carbendazim are toxic to the cells of plant-beneficial rhizobacteria. This suggests that a recommended dose of fungicide should be made to lessen its harmful effects.